Student perceptions of the teaching in online learning: and Australian university case study - Tucker, Beatrice; Halloran, Patrick; Price, Connie (HERDSA, 2013)
Universities have been collecting student feedback on their experiences in teaching and learning for decades. Their voice is usually captured in surveys with quantitative and qualitative data used for quality improvement. Quantitative data are often used to monitor the student experience and used as a key performance measure. As online learning is increasingly taken up in universities there is heightened interest about the student experience. In Australia, Open Universities Australia is the largest national provider of online learning. This paper analyses student perceptions of what is helping and hindering their learning, with a focus on teaching, from one large shareholder university. The eVALUate unit survey was used to collect student feedback from 47696enrolling students in 490 units delivered over seven OUA study periods during 2012. The overall response rate for the unit survey was 24.1%. Students overwhelmingly reported very high levels of satisfaction with their experience. In selected units there were lower levels of satisfaction for quality of teaching and feedback on learning. Students commented that the online interactions with the teacher were most important to their learning and where feedback on their learning and assessments was not provided, this hindering their learning. Hence giving students feedback is an important role of the teacher in helping them learn online.